IMINOAMINOSULFINATES - SYNTHESIS, CRYSTAL-STRUCTURES, AND REARRANGEMENT MONITORED BY LI-7 SOLID-STATE NUCLEAR-MAGNETIC-RESONANCE SPECTROSCOPY - FREITAG, S; Kolodziejski, W; Pauer, F; Stalke, D (Dalton Transactions, 1993)
Alkali- and alkaline-earth-metal iminoaminosulfinates have been synthesised and characterized by X-ray diffraction and solid-state NMR investigations. The viability of metal-exchange reactions has been demonstrated resulting in a magnesium and a copper(I) derivative. The structural investigations reveal the presence of different structures, which can be classified into four types. Phase transitions between different structural types involving the loss of donor solvent have been observed by solid-state magic angle spinning experiments.